The Mediating Effect of Financial Literacy on Blockchain Technology Application and Financial Risk: Insight from Ghanaian Professionals towards Policy Recommendations - Okpoti, Maxwell Mensah; Peprah, Williams Kwasi (International Journal of Economics and Financial Issues, 2024)
This study explores the mediating effect of financial literacy on the relationship between blockchain technology application and financial risk among financial institution professionals in Ghana. Utilizing a correlational research design, data were collected from a sample of 336 professionals through a self-constructed Likert-scale questionnaire. The analysis was conducted using path analysis and mediation techniques. The findings reveal that financial literacy had a significant partial mediating effect between blockchain technology application and financial risk, accounting for 26.0% of the total effect. The direct negative effect of blockchain technology applications on financial risk also remained significant, highlighting the independent contribution of blockchain technology applications to reducing financial risk. These results underscore the importance of financial literacy in enhancing the effectiveness of blockchain technology applications in mitigating financial risks. The study emphasizes the need for comprehensive financial literacy programs to maximize the benefits of technological advancements in the financial sector. Empirical evidence from related literature supports the findings, indicating that higher financial literacy enables better utilization of blockchain technology applications, thereby reducing financial risk. The research provides insights for policymakers aiming to improve financial literacy and leverage blockchain technology applications for financial risk management.